Culture and emotion in Paralympic swimming medalists - Jeffrey J. Martin; Erin Snapp; Franziska Loetzner; Fatemeh Dehghan; Eva Prokešová; Tania Bastos (Karolinum Press, 2022)
The purpose of the present study was to examine if cultural identity was related to the emotional experiences of Paralympic (N = 83) swimmers' upon winning medals at the 2016 Paralympic Games. Paralympic athletes' countries (N = 5) were scored on Hofstede's (2011) six cultural dimensions and athletes who won medals had their facial expressions analyzed to determine levels of basic emotions (i.e., happiness, sadness, anger, surprise, disgust, fear, and neutral) based on Ekman's (1993) neuro-cultural theory of emotion. After controlling for medal won, and time and place expectation proxies, we found that happiness was negatively associated with long/short term orientation (r = -0.313, p < 0.004) and positively linked to indulgence/restraint (r = 0.210, p < 0.06). The emotion of neutral was positively associated with power distance (r = 0.239, p < 0.032) and long term/short term orientation (r = 0.290, p < 0.009) while being negatively linked to indulgence (r = -0.276, p < 0.013). Based on an abductive theory of the scientific method (Haig, 2005; 2008) we formed plausible theory-based explanations for our findings and concluded, given our study is the first of its nature, that researchers should continue this line of inquiry.